Analisis kualitas sumber daya manusia sebagai pendukung peningkatan kinerja karyawan pada PT MNC sekuritas - Alit Witsqa Fazrin; Santi Afganistan; Andriana Kristina R Simamora (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Every company is formed to achieve certain goals and if achieved can be said to be successful. To achieve success, competent human resources are needed. Thus human resources can be useful for the organization and improve performance. The purpose of this study is to analyze and find out the strategies implemented in improving the performance of human resources and potential at PT MNC Sekuritas. Where the data collection by seeking information directly to the informant (interview). Based on the research conducted, it can be concluded that there is a significant influence of human resources on improving employee performance and career development can provide changes to job satisfaction and have a positive influence.